The 2nd International Electronic Conference on Water Sciences 2017
DOI: 10.3390/ecws-2-04956
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phytoplankton Blooms under the Index of Inherent Optical Properties (IOP Index)

Abstract: . The diversity of sites shows that the IOP index is a suitable method to determine the bloom conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…The turbidity patterns obtained from the Secchi disk readings indicated that the concentration of suspended material particles shows a persistent southward gradient with the highest values for CDR area and intertidal zone. The research of Aguilar-Maldonado et al (2017), showed the predominance of detritus against coloured dissolved organic matter and phytoplankton in the CDR area. Thus, the observed high reflectances are associated with suspended particulate matter, and higher turbidity.…”
Section: Resultsmentioning
confidence: 93%
“…The turbidity patterns obtained from the Secchi disk readings indicated that the concentration of suspended material particles shows a persistent southward gradient with the highest values for CDR area and intertidal zone. The research of Aguilar-Maldonado et al (2017), showed the predominance of detritus against coloured dissolved organic matter and phytoplankton in the CDR area. Thus, the observed high reflectances are associated with suspended particulate matter, and higher turbidity.…”
Section: Resultsmentioning
confidence: 93%
“…The high-density HABs formed by Scrippsiella, a genus of nontoxic, cosmopolitan marine dinoflagellates, lead to oxygen depletion and therefore fish kills (6). Scrippsiella blooms have been reported worldwide, including in China (7-10), Ukraine (11), Spain (12), the southern Red Sea (13), Mediterranean Sea (14,15), the Atlantic and Pacific coasts of Mexico (16)(17)(18)(19), Australia (6), the Atlantic coast of the USA (20), and the southeast coast of Iran (21). Although little is known about the physiology of this genus, its large physiological, morphological, and genetic variability suggest the existence of cryptic species.…”
mentioning
confidence: 99%